UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR KARET KE JERMAN TAHUN 2019-2023 - Affandi, Muhammad Raihan; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Rubber is an elastic and dense plantation sector material. Commodities used in everyday equipment include natural rubber and synthetic rubber. Indonesia's rubber plantations are dominated by state-owned smallholder plantations and the main producers excel in export and import activities. Indonesia as a form of competitiveness has the aim of winning competition in international trade. Therefore, Indonesia plays an important role in strengthening economic development and exporting rubber to Germany. This research is qualitative research with secondary data collection taken from journals, news and official websites. This thesis is in accordance with the theme of using international trade theory put forward by Adam Smith and David Ricardo with a focus on the economic elements of international trade. Indonesia exports rubber to Germany as a form of international trade to increase competitiveness and promote the welfare of Indonesian rubber commodities. Indonesia is ranked second with the largest rubber commodity in the world. However, the causes related to the decline in Indonesian rubber commodities are experiencing obstacles such as falling interest prices, COVID-19, and commodity shifts. Keywords: Indonesia, Germany, Export, Rubber, Commodity